Lung Abscess Located in Lesion of Lung Tumor and Multiple Cavities due to Pulmonary Tuberculosis: A Case Report - Indriani, Sri Indah; Simatupang, Elvando Tunggul Mauliate; Wibowo, Adityo; Makmur, Andreas; Fidiawati, Wiwit Ade (Jurnal Respirasi, 2024)
Introduction: People with tuberculosis (TB) have an increased risk of pulmonary cancer. They are also disproportionately affected by risk factors like immune suppression, smoking, and alcohol misuse. A lung tumor is reported to have occurred after an episode of TB, but we reported a patient with a lung tumor with co-infection TB and lung abscess at the same time. Case: A 73-year-old man was hospitalized at Arifin Achmad General Hospital, Pekanbaru, with a 3-day history of bloody cough 2-3 times a day, 1-2 tablespoons estimated by the patient for blood from the cough. The patient had a cough with white phlegm in the last 4 months before the bloody cough. The patient also had a fever, night sweats, a limp body, decreased appetite for 6 months, and decreased body weight by 15 kg in the last year. Heterogenic consolidation on the superior lobe of the lung with prominence compression and irregular boundaries in the apex was found. We found an air bronchogram and multiple cavities with air-fluid levels inside the lesion. We also found a satellite nodule in the inferior lung and a mass connected with the chest wall. GeneXpert showed low detection for Mycobacterium tuberculosis. The patient was diagnosed with a left lung abscess, pulmonary TB, left lung tumor T4N2M1a, unspecified type of tumor stage IVA PS2, and osteoporosis. Conclusion: Lung tumors could also be diagnosed with co-infection TB. Proper diagnosis to make sure cancer and TB are co-infected is necessary. Therefore, it will not be just a single disease that is treated.